DIXDC1 promotes tumor proliferation and cell adhesion mediated drug resistance (CAM-DR) via enhancing p-Akt in Non-Hodgkin's lymphomas. (November 2016) - Ouyang, Yu; Zhong, Fei; Wang, Qiru; Ding, Linlin; Zhang, Peipei; Chen, Lingling; Wang, Yuchan; Cheng, Chun
Highlights: Adhesion of NHL cell lines to HS-5 or FN inhibited cytotoxic drug-induced apoptosis. DIXDC1 promoted cell adhesion-mediated drug resistance via the AKT pathway. DIXDC1 is a potential therapeutic target for overcoming cell adhesion-mediated drug resistance in NHL. Abstract: DIX domain containing 1 (DIXDC1), is a human homolog of Ccd1, a DIX domain containing protein in zebrafish. The present study was undertaken to determine the expression and biologic function of DIXDC1 in Non-Hodgkin's lymphoma (NHL). Clinically, we detected that the expression of DIXDC1 was significantly lower in the indolent lymphomas compared with the progressive lymphomas by immunohistochemistry analysis. Functionally, we found that DIXDC1 could promote cell proliferation via modulating cell cycle progression and PI3K/AKT signaling pathway in NHLs. Moreover, we confirmed that DIXDC1 was involved in the process of lymphoma cell adhesion mediated drug resistance (CAM-DR). Adhesion to fibronectin (FN) or HS-5 up-regulated DIXDC1 expression, and up-regulation of DIXDC1 resulted in an increased expression of p-AKT, which promoted CAM-DR. Our finding supports the role of DIXDC1 in cell proliferation, cell cycle and CAM-DR in NHLs. We propose that inhibition of DIXDC1 expression may be a novel therapeutic approach for NHLs patients, and it may be a target for drug resistance.